2014
DOI: 10.1089/thy.2014.0134
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E in Papillary Thyroid Carcinoma Is Associated with Increased Programmed Death Ligand 1 Expression and Suppressive Immune Cell Infiltration

Abstract: Background: There remain a small number of patients with papillary thyroid cancer (PTC) who suffer recurrence, metastases, or death. While mutation of the BRAF gene, corresponding to the constitutively active BRAF V600E protein, has been associated with worse clinical outcomes in thyroid cancer, the reasons underlying this observation are presently unknown. Disruption of endogenous host immune surveillance and promotion of tumor immune escape is one mechanism by which BRAF V600E tumors may achieve more aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 55 publications
16
105
1
1
Order By: Relevance
“…These results demonstrate that a strongly immunosuppressive molecular profile may be elicited in the tumor microenvironment of papillary thyroid carcinomas positive for the BRAF V600E mutation, suggesting that the promotion of tumor immune escape may be a mechanism by which the BRAF V600E mutation may contribute to aggressive tumor behavior (Angell et al 2014). Following this rationale, Brauner and coworkers thoroughly investigated the PD-1/PD-L1 immune checkpoint mechanism in a thyroid cancer model (Brauner et al 2016).…”
Section: :12mentioning
confidence: 95%
See 1 more Smart Citation
“…These results demonstrate that a strongly immunosuppressive molecular profile may be elicited in the tumor microenvironment of papillary thyroid carcinomas positive for the BRAF V600E mutation, suggesting that the promotion of tumor immune escape may be a mechanism by which the BRAF V600E mutation may contribute to aggressive tumor behavior (Angell et al 2014). Following this rationale, Brauner and coworkers thoroughly investigated the PD-1/PD-L1 immune checkpoint mechanism in a thyroid cancer model (Brauner et al 2016).…”
Section: :12mentioning
confidence: 95%
“…Angell and coworkers demonstrated that papillary thyroid carcinomas harboring the BRAF V600E mutation frequently express PD-L1 (Angell et al 2014). Similarly, positivity for the BRAF V600E mutation was associated with the expression of HLA-G (a nonclassical and inhibitory MHC class I molecule).…”
Section: Immune Checkpoint Inhibitors For Treating Thyroid Cancermentioning
confidence: 99%
“…The latter findings suggest a Braf-driven tumor-promoting microenvironment. 103 CD4 C cells CD4 C T helper (Th) lymphocytes are a heterogeneous population. Th1-mediated immunity is generally considered as antitumoral, while polarized Th2 and/or Treg activity is believed protumorigenic.…”
Section: Natural Killer T Cells (Nkt) Gd T Cells and Innate Lymphoidmentioning
confidence: 99%
“…In contrast, BRAF V600E positivity had no impact on TAM (CD68+ or CD163+ positive macrophages) content in PTCs (Angell et al 2014). This observation leads to the hitherto unresolved question whether mutational features and/or load (e.g.…”
Section: :10mentioning
confidence: 94%
“…Several studies have shown a correlation of tumor PD-L1 expression and response to anti-PD-1/ PD-L1 treatment (Herbst et al 2014, Borghaei et al 2015, Garon et al 2015, whilst others did not (Larkin et al 2015, McDaniela 2015, Robert et al 2015b. Furthermore, one methodological problem using PD-L1 as a single biomarker might be that different antibodies are Angell et al 2014, Robert et al 2015a. In addition, harmonization of IHC protocols and definition of reliable cut-offs for quantification of PD-L1 staining is still missing with most tests focusing on PD-L1 expression on tumor cells (Borghaei et al 2015) while others also include myeloid cells (Herbst et al 2014).…”
Section: :10mentioning
confidence: 99%